Real-time running event detection via a community patrol robot. (14th November 2016) - Cai, Shibo; Guo, Huiwen; Bao, Guanjun; Wu, Xinyu; Li, Nannan
Security surveillance is an important application for patrol robots. In this article, a real-time running event detection method is proposed for the community patrol robot. Although sliding window-based approaches have been quite successful in detecting objects in images, directly extending them to real-time object detection in video is not simple. This is due to the huge samples and diversity of object appearances with multivisual view and scale. To address these limitations, first, a simple and effective spatial–temporal filtering-based approach is proposed to obtain moving object proposals in each frame; then, two-stream convolutional networks fusion architecture is introduced to best take advantage of the spatial–temporal information from the proposal. The algorithm is applied on PatrolBot in community environments and runs at 15 fps on a consumer laptop. Two benchmark data sets (the Kungliga Tekniska Högskolan [KTH] data set and Nanyang Technological University [NTU] running data set) were also used to compare results with previous works. Experimental results show higher accuracy and lower detection error rate in the proposed method.